Development of a Scientific Approach-Based Pocketbook (5M) on the Diversity of Boss Plants in the Sari Embun Lake Area, Tanah Laut Regency - Fahira Ramadhani; Sri Amintarti; Amalia Rezeki (Universal Education, 2024)
The presence of moss in the environment can be used as a source of student learning. The advantages of using the environment as a learning resource are that it makes students get information based on direct experience, is more communicative, makes lessons more real, and makes students know and love the environment. The purpose of this study was to describe the feasibility, suitability, legibility, and response of students to the pocket book of moss plants around the Sari Dew Lake, Tanah Laut Regency. This research is a research and development with a 4-D (four D) development model. The results of the development of a pocket book based on (5M) material on the diversity of moss plants in the area of Danau Sari Embun, Tanah Laut Regency, obtained an average suitability score of 4.52 for expert subjects, which is categorized as very suitable for learning objectives. The feasibility test got an average feasibility score from expert subjects of 4.33, which was included in the very worthy category for use as a learning material. The readability test got an average readability score by students of 90.45% which was included in the very good category for students to read. The student response test got an average score of 4.67, which was included in the very positive category when used as a learning material in the learning process. Research on the diversity of organisms in the area of Lake Sari Embun, Tanah Laut Regency, can still explore the potential related to local wisdom. Efforts to promote and introduce the Sari Dew lake area are needed so that the area can be utilized optimally, especially in the field of education.